2011
DOI: 10.1080/01431161.2010.549853
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal and temporal evolution of raindrop size distribution observed over a tropical station using a K-band radar

Abstract: Rain drop size distribution (DSD) measurements at different heights were made using a micro rain radar (MRR) at Thiruvananthapuram (latitude: 8.3 • N, longitude: 76.9 • E). Rain DSD data obtained from the MRR have been compared with a Joss-Waldvogel impact-type disdrometer (RD-80) deployed nearby and found to have good agreement. The analysis uses data collected during 16 continuous rainfall episodes during the southwest monsoon (June to September, JJAS) season. Since all the episodes behaved similarly, a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…The differences in N w and D m comparisons for CR category might be related to the strong vertical variations in convective systems or may be due to the detecting sensitivities of the two instruments to different raindrops. Although that the 2DVD can detect raindrops with diameter between 0.1 and 8.1 mm and the MRR can only detect raindrops with diameter between 0.246 and 5.03 mm, Harikumar et al () found that the MRR overestimated the number concentration of small raindrops and underestimated the number concentration of large raindrops, corresponding to higher N w and lower D m in CR category. Another source for the bias is that some of small raindrops fail to reach the ground due to the evaporation process, leading to fewer number concentration of small raindrops observed by the 2DVD.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The differences in N w and D m comparisons for CR category might be related to the strong vertical variations in convective systems or may be due to the detecting sensitivities of the two instruments to different raindrops. Although that the 2DVD can detect raindrops with diameter between 0.1 and 8.1 mm and the MRR can only detect raindrops with diameter between 0.246 and 5.03 mm, Harikumar et al () found that the MRR overestimated the number concentration of small raindrops and underestimated the number concentration of large raindrops, corresponding to higher N w and lower D m in CR category. Another source for the bias is that some of small raindrops fail to reach the ground due to the evaporation process, leading to fewer number concentration of small raindrops observed by the 2DVD.…”
Section: Resultsmentioning
confidence: 98%
“…Over the past few decades, studies regarding to MRR mainly focused on the characteristics of the DSDs and the Z‐R relationships. Harikumar et al () noted that the vertical variations of the DSDs were usually caused by the evolution processes of perceptible particles via melting, coalescence, break‐up, and evaporation, which were associated with precipitation types, geographical locations, and climatic regimes (Rosenfeld & Ulbrich, ; Tokay et al, ). An integrative study of both MRR and two‐dimensional video disdrometer (2DVD) measurements during a BBC‐2 campaign in Cabauw (Netherlands) showed that a highly variable and ambiguous Z‐R relationship was strongly related to the DSD (Diederich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…DSD characteristics are related to processes such as hydrometeor condensation, coalescence, and evaporation. In addition, the altitudinal variations in DSD parameters provide the cloud and rain microphysical processes (Harikumar et al, 2012). These are important parameters affecting the microphysical processes in the parameterization schemes of numerical models (Gao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of RSDs focus on their variability in different rain types and climate regimes, while few studies consider their vertical structure. The vertical structure of RSDs can be measured by two or more surface instruments positioned at different altitudes on a mountain (Levin et al 1991), as well as by an airborne particle measuring system (Jia and Niu 2008) or vertical pointing radar (VPR) (Cifelli et al 2000;Blahak and Beheng 2001;Peters et al 2005;Tokay et al 2009;Yoshikawa et al 2010;Harikumar, Sampath, and Sasi Kumar 2012;Ruan et al 2014). Compared with ground measurements along a mountain slope and airborne measurements, observations of vertical microphysical variables using VPRs are more temporally and spatially consistent.…”
Section: Introductionmentioning
confidence: 97%
“…The characteristics of vertical RSDs, such as the total number concentration, radar reflectivity Z, rain rate R, and the Z-R relationship, have been presented using VPRs (Cifelli et al 2000;Tokay et al 2009;Harikumar, Sampath, and Sasi Kumar 2012;Ruan et al 2014). The results of such studies have shown that significant differences occur in the mean rainfall parameters and Z-R relationships for each rainfall category (stratiform/convective) as a function of height, especially in a convective rainfall event.…”
Section: Introductionmentioning
confidence: 99%